Fatigue life prediction of thermal barrier coatings using a simplified crack growth model. Issue 5 (May 2019) - Jonnalagadda, Krishna Praveen; Eriksson, Robert; Li, Xin-Hai; Peng, Ru Lin
Abstract: Models that can predict the life of thermal barrier coatings (TBCs) during thermal cycling fatigue (TCF) tests are highly desirable. The present work focuses on developing and validating a simplified model based on the relation between the energy release rate and the TCF cycles to failure. The model accounts for stresses due to thermal mismatch, influence of sintering, and the growth of TGO (alumina and other non-protective oxides). The experimental investigation of TBCs included; 1) TCF tests at maximum temperatures of 1050 °C, 1100 °C, 1150 °C and a minimum temperature of 100 °C with 1 h and 5 h (1100 °C) hold times. 2) Isothermal oxidation tests at 900, 1000 and 1100 °C for times up to 8000 h. The model was calibrated and validated with the experimental results. It has been shown that the model is able to predict the TCF life and effect of hold time with good accuracy.